Total substitution and partial modification of the set of non-ribosomal peptide synthetases clusters lead to pyoverdine diversity in the Pseudomonas fluorescens complex - Graña-Miraglia, Lucía; Geney Higuita, Jorge Luis; Salazar, Juan Carlos; Guaya Iñiguez, Diana; Alcolado León, Carlos; García-Angulo, Víctor A. (Frontiers in Microbiology, 2024)
Pyoverdines are high affinity siderophores produced by most Pseudomonas with a wide role in microbial interspecies interactions. They are primarily composed of a conserved chromophore moiety, an acyl side chain and a peptide backbone which may be highly variable among strains. Upon ferric iron sequestration, pyoverdines are internalized through specialized receptors. The peptide precursor of pyoverdine, termed ferribactin, is synthesized by a set of non-ribosomal peptide synthetase (NRPS) enzymes and further modified by tailoring enzymes. While PvdL, the NRPS responsible for the synthesis of the peptide moiety that derives into the chromophore is conserved, the NRPSs for the peptide backbone are different across fluorescent Pseudomonas. Although the variation of pyoverdine is a widely recognized characteristic within the genus, the evolutionary events associated with the diversity and distribution of this trait remain mostly unknown. This study analyzed the NRPSs clusters for the biosynthesis of the peptide backbone of ferribactin in the genomes of a representative subset of strains of the Pseudomonas fluorescens complex. Bioinformatic analysis of the specificity of adenylation domains of the NRPSs allowed the prediction of thirty different pyoverdine variants. Phylogenetic reconstruction and mapping of the NRPS clusters pinpointed two different general levels of modifications. In the first level, a complete replacement of the set of NRPRs by horizontal transfer occurs. In the second level, the original set of NRPSs is modified through different mechanisms, including partial substitution of the NRPS genes by horizontal transfer, adenylation domain specificity change or NRPS accessory domain gain/loss.